Smart Interactive Braille Periodic Table: An Assistive Learning Technology for Inclusive Chemistry Education for Visually Impaired Students - Siti Aisatul Hijriyah; Kusumawati Dwiningsih; Inka Putri Suryani; Nina Ayu Firnanda; Haykal Aulil Albab; Wanda Istian Hamidah; Maharani Agustina Arivi (Universitas Syiah Kuala, 2026)
The abstract nature of chemistry poses significant learning challenges for visually impaired students, highlighting the need for tactile-based assistive learning technologies such as Braille to support inclusive chemistry education. This study aims to develop a smart interactive braille periodic table with dynamic audio as an assistive learning technology for inclusive chemistry learning. Limited access to visual learning resources poses significant challenges for visually impaired students in understanding the periodic system of elements. This study uses the research and development (R&D) method with the ADDIE model which is limited to the implementation stage (analysis, design, development, implementation. The developed media integrates tactile Braille, dynamic audio feedback, and a smart interactive system to provide real-time multisensory learning experiences for visually impaired students. The results showed that the media achieved high validity, with content validity of 87% and construct validity of 89%. The practicality test indicated very high usability, with student responses reaching 89.28% and learning activity observations achieving 100%. The effectiveness test demonstrated a significant improvement in learning outcomes, with an N-Gain score of 88.15% (very high) and a significant difference between pretest and posttest scores (p < 0.05). In conclusion, the smart interactive braille periodic table is a valid, practical, and effective assistive learning technology that enhances accessibility and conceptual understanding in inclusive chemistry learning